Assessment of Indian wheat germplasm for Septoria nodorum blotch and tan spot reveals new QTLs conferring resistance along with recessive alleles of Tsn1 and Snn3 - Sudhir Navathe; Xinyao He; Kamble, Umesh; Kumar, Manjeet; Patial, Madhu; Singh, Gyanendra; Singh, Gyanendra Pratap; Joshi, Arun Kumar; Singh, Pawan Kumar (Frontiers Media, 2023)
The leaf blight diseases, Septoria nodorum blotch (SNB), and tan spot (TS) are emerging due to changing climatic conditions in the northern parts of India. We screened 296 bread wheat cultivars released in India over the past 20 years for seedling resistance against SNB (three experiments) and TS (two experiments). According to a genome-wide association study, six QTLs on chromosome arms 1BL, 2AS, 5BL, and 6BL were particularly significant for SNB across all three years, of which Q.CIM.snb.1BL, Q.CIM.snb.2AS1, Q.CIM.snb.2AS.2, and Q.CIM.snb.6BL appeared novel. In contrast, those on 5BS and 5BL may correspond to Snn3 and Tsn1, respectively. The allelic combination of tsn1/snn3 conferred resistance to SNB, whereas that of Tsn1/Snn3 conferred high susceptibility. As for TS, Tsn1 was the only stably significant locus identified in this panel. Several varieties like PBW 771, DBW 277, and HD 3319, were identified as highly resistant to both diseases that can be used in future wheat improvement programs as resistant donors.